Evidence of perceived psychosocial stress as a risk factor for stroke in adults: a meta-analysis - Booth J; Connelly L; Lawrence M; Chalmers C; Joice S; Becker C; Dougall N (BioMed Central, 2015)
Abstract Background : Several studies suggest that perceived psychosocial stress is associated with increased risk of stroke; however results are inconsistent with regard to definitions and measurement of perceived stress, features of individual study design, study conduct and conclusions drawn and no meta-analysis has yet been published. We performed a systematic review and meta-analysis of studies assessing association between perceived psychosocial stress and risk of stroke in adults.The results of the meta-analysis are presented. Methods: Systematic searches of MEDLINE, EMBASE, CINAHL, PsycInfo, and Cochrane Database of Systematic Reviews were undertaken between 1980 and June 2014. Data extraction and quality appraisal was performed by two independent reviewers. Hazard ratios (HR) and odds ratios (OR) were pooled where appropriate. Results: 14 studies were included in the meta-analysis, 10 prospective cohort, 4 case–control design. Overall pooled adjusted effect estimate for risk of total stroke in subjects exposed to general or work stress or to stressful life events was 1.33 (95 % confidence interval [CI], 1.17, 1.50; P < 0.00001). Sub-group analyses showed perceived psychosocial stress to be associated with increased risk of fatal stroke (HR 1.45 95 % CI, 1.19,1.78; P = 0.0002), total ischaemic stroke (HR 1.40 95 % CI, 1.00,1.97; P = 0.05) and total haemorrhagic stroke (HR 1.73 95 % CI, 1.33,2.25; P > 0.0001).A sex difference was noted with higher stroke risk identified for women (HR 1.90 95 % CI, 1.4, 2.56: P < 0.0001) compared to men (HR 1.24 95 % CI, 1.12, 1.36; P < 0.0001). Conclusions: Current evidence indicates that perceived psychosocial stress is independently associated with increased risk of stroke.
Keywords: Stress; Psychological; Stroke; Risk factor; 1109 Neurosciences; 1702 Cognitive Sciences